2022
DOI: 10.1136/bmjoq-2022-002033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a novel, integrative dashboard for health professionals’ performance in managing deteriorating patients:a quality improvement project

Abstract: BackgroundThe quality of recording and documentation of deteriorating patient management by health professionals has been challenged during the COVID-19 pandemic. Non-adherence to escalation and documentation guidelines increases risk of serious adverse events. Electronic health record (EHR)-integrated dashboards are auditing tools of patients’ status and clinicians’ performance, but neither the views nor the performance of health professionals have been assessed, relating to management of deteriorating patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…4,8,9 Previous research in this field has demonstrated that technological solutions, such as widely visible EMR-based dashboards for monitoring multiple patients may effectively reduce the time required to prioritize patients in need of immediate care, improve the accuracy of assigning priorities, and alleviate the cognitive burden on clinical staff. 10,11 These tools may facilitate team communication, overcoming the challenges of fragmented data, 4 and, by enhancing communication and situational awareness, also improve teamwork. 12 Research to date has primarily evaluated interfaces designed for individual use rather than those intended for display on a large screen and accessible by multiple users within a shared space.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…4,8,9 Previous research in this field has demonstrated that technological solutions, such as widely visible EMR-based dashboards for monitoring multiple patients may effectively reduce the time required to prioritize patients in need of immediate care, improve the accuracy of assigning priorities, and alleviate the cognitive burden on clinical staff. 10,11 These tools may facilitate team communication, overcoming the challenges of fragmented data, 4 and, by enhancing communication and situational awareness, also improve teamwork. 12 Research to date has primarily evaluated interfaces designed for individual use rather than those intended for display on a large screen and accessible by multiple users within a shared space.…”
Section: Background and Significancementioning
confidence: 99%
“…EMR-based multi-patient dashboards have shown promise in supporting clinicians with their workload and improving situational awareness in the ICU [4,8,9] . Previous research in this field has demonstrated that technological solutions, such as widely visible EMR-based dashboards for monitoring multiple patients may effectively reduce the time required to prioritize patients in need of immediate care, improve the accuracy of assigning priorities, and alleviate the cognitive burden on clinical staff [10,11] . These tools may facilitate team communication, overcoming the challenges of fragmented data [4] , and, by enhancing communication and situational awareness, also improve teamwork [12] .…”
mentioning
confidence: 99%
“…Powerful antibiotics with a broad-spectrum can treat a range of infections and are particularly valuable when clinicians are uncertain about the exact cause. In an effort to surmount the intricate intricacies associated with this matter, anyone entering a hospital with clinical features is flagged as having sepsis and should be prescribed broad-spectrum antibiotics within an hour [48]. But this -better safe than sorry‖ approach can have unintended ramifications of AMR [49].…”
Section: Impact Of Antimicrobial Resistance On Sepsismentioning
confidence: 99%
“…Temuan ini koheren dengan studi di departemen rumah sakit yang berbeda di mana kursus Pendidikan Komunikasi Kolaboratif SBAR telah dilaksanakan. Dalam studi oleh (Alhmoud et al, 2022) penerapan SBAR terbukti membantu perawat lebih fokus dan memudahkan komunikasi mereka selama serah terima. Demikian pula, (Dalky et al, 2020) menemukan bahwa implementasi SBAR memiliki efek positif pada perawat kebidanan sehubungan dengan kepuasan kerja, kondisi kerja, iklim keselamatan, dan kerja tim.…”
Section: Hasil Penelitianunclassified